2023
DOI: 10.1002/jnr.25231
|View full text |Cite
|
Sign up to set email alerts
|

Plasma versus serum for extracellular vesicle (EV) isolation: A duel for reproducibility and accuracy for CNS‐originating EVs biomarker analysis

Abstract: Blood‐derived extracellular vesicles (EVs) are a popular source of biomarkers for central nervous system (CNS) diseases, but inconsistencies in isolation and analysis hinder their clinical translation. This review summarizes recent studies that investigate the impact of different anticoagulated plasma and serum on the yield, purity, and molecular content of EVs. Specifically, the studies compare ethylenediaminetetraacetic acid (EDTA), citrate, heparin plasma, and serum and highlight the risk of contamination f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Publication bias analyses showed that smaller studies with non-significant or low effects size results have been less likely to be published. Unsurprisingly, this is to be expected as alluded to previously [ 40 , 41 ], there has been consistent failure of independent validation across studies using speculative CNS-enriched EVs, likely due to EVs being very sensitive to various pre-analytical factors [ 40 ], high complexity of methodologies used to isolate speculative CNS-enriched EVs as well as user differences in handling, among others. Even though measuring biomarkers in speculative CNS-enriched EVs for patients with PD vs HCs has been popular since 2014, only few studies currently exist, further indicating that studies with null results might not have been published.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Publication bias analyses showed that smaller studies with non-significant or low effects size results have been less likely to be published. Unsurprisingly, this is to be expected as alluded to previously [ 40 , 41 ], there has been consistent failure of independent validation across studies using speculative CNS-enriched EVs, likely due to EVs being very sensitive to various pre-analytical factors [ 40 ], high complexity of methodologies used to isolate speculative CNS-enriched EVs as well as user differences in handling, among others. Even though measuring biomarkers in speculative CNS-enriched EVs for patients with PD vs HCs has been popular since 2014, only few studies currently exist, further indicating that studies with null results might not have been published.…”
Section: Resultsmentioning
confidence: 77%
“…As previously indicated [ 40 – 42 ], several pre-analytical elements can have a substantial effect on the purity, content, dimensions, and amount of EVs. Such elements involve the selection of anticoagulation molecules mixed with plasma, EV isolation methodology, the centrifugation procedure, the transportation characteristics, the frequency of freezing and thawing cycles, the storage parameters, the temperature, and the type of tube used for collection.…”
Section: Resultsmentioning
confidence: 91%
“…Acknowledging that platelets show circadian rhythmicity, peaking in the morning [153], which in part contributes to platelets having the largest number of EVs in the blood [154], and given the circadian nature of cargoes derived from EVs [155], we considered the timing of collection in our examination of diagnostic accuracy, especially since platelet depletion is commonly overlooked before EV isolation. For both general EVs ( Figure S8A-C ) and speculative CNS-enriched EVs ( Figure S9A-C ), the diagnostic accuracy was consistently higher for studies who obtained their samples in the afternoon vs. the morning ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous review [154], we compared the usage of different anticoagulant molecules on EV isolation and biomarker analysis, and underscored the advantage of using citrate over EDTA and heparin to reduce noise introduced to the biomarker measurements from EVs, which was recently supported by a large comparative study [156]. Our comparative analysis of the diagnostic accuracy using general EVs ( Figure S12A-C ) or speculative CNS-enriched EVs ( Figure S13A-C ) demonstrated that studies using citrate did indeed achieve a higher diagnostic accuracy compared to EDTA ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the size, purity, content, and reliability of EVs depends on the liquid and methodology of isolation [100][101][102][103], we compared the diagnostic metrics by CSF, plasma, and serum. We did not include urine or saliva due to the inclusion of only 2 studies for each.…”
Section: Pd Vs Control By Mediummentioning
confidence: 99%